Influence of gender disparity in predicting occurrence of successful aging, usual aging and mild cognitive impairment - Vanoh, Divya; Sahar, Suzana; Razali, Rosdinom; Abdul Manaf, Zaharah; Tengku Abdul Hamid, Tengku Aizan (Elsevier, 2019)
Background: The aim of this study was to investigate the prevalence of successful aging, usual aging and mild cognitive impairment among older men and women, and further determine the influence of gender in predicting cognitive decline. Method: A total of 1,993 respondents aged 60 years old and above were selected through a multi-stage random sampling method from Johor, Kelantan, Selangor and Perak. The respondents were interviewed to obtain information on socio-demography, diet, cognitive functions, psychosocial conditions and lifestyle. Subjects were classified in either the category of successful aging, usual aging and mild cognitive impairment. Results: The predictors of cognitive decline among men were poor upper body flexibility and lower body strength, higher fasting blood sugar, hyperlipidaemia, lower education level, and poor participation in mechanical repairing activities. Meanwhile, hyperlipidaemia, not adhering to calorie restrictions, poor lower body flexibility, disabilities and lower education status were the risk factors for memory impairment among women. Conclusion: Specific gender-tailored interventions are essential for preventing or managing cognitive decline among older adults and preserving mental health